Analysis of Digital Marketing 4C in Convection MSMEs in the Era of Society 5.0 - Gian Riksa Wibawa; Arif Arif; Muhammad Irsal Muharrom; Luviany Kastury; Andra Kharuna Pratama; Sofie Aulia; Febi Ferbianti (Universitas KH. Abdul Chalim Mojokerto, 2024)
This research aims to determine and analyze 4C Digital Marketing in convection MSMEs in the Society 5.0 Era in Tasikmalaya City and Tasikmalaya Regency. This research is qualitative research with a qualitative descriptive approach. The data collection techniques used were observation, interviews with 50 informants from 50 convection MSMEs, and documentation studies. The object of this research is aimed at convection business owners located in the Tasikmalaya City and Tasikmalaya Regency areas. In terms of Co-Creation, in producing products, the MSME convection business has produced products according to consumers' ideas and desires, apart from that, some follow trends. In determining the prices of their products, these business actors have adjusted prices to consumers' purchasing power. This is in accordance with Currency where in this digital era prices are more dynamic. These convection business actors have utilized Communal Activities in their business, this can be seen from the existence of resellers and drop shippers who have become partners in the distribution and marketing of their business products, in addition to word-of-mouth marketing or what is better known as word-of-mouth marketing. In terms of conversation, these MSME convection actors have responded quickly in answering questions from potential consumers. Apart from that, several convection MSMEs have used social media to go live so that they can facilitate potential consumers to ask questions regarding products, which can be answered directly by these convection business actors. Apart from that, reviews and ratings from consumers can provide trust and influence other potential consumers.